Social Enterprise: Generasi Muda Berbisnis serta Berdampak Positif - Tjun Tjun, Lauw; Mariana, Ana; Nur, Nur; Lunandi, Yenny Yuniawaty; Nurbasari, Anny; Liliawati, Swat Lie (Universitas Prof. Dr. Moestopo (Beragama), 2026)
On January 7 and 14, 2023, a Community Service program was conducted for the youth of GJKI Andir Bandung, attended by 33 participants. This activity was related to social enterprise. A social enterprise is a business model that combines social goals with commercial strategies, where profits are used to achieve positive impacts on society or the environment. It aims to create sustainable social value, such as poverty alleviation, community empowerment, or environmental preservation. While operating within a business framework, success is measured not only by profit but also by their contribution to social or environmental improvements. The youth of GJKI Bandung aim to contribute to sustainable social value, leveraging their remarkable potential and diverse educational backgrounds. The activity was carried out in the form of training, discussions, and question-and-answer sessions. Based on participants' evaluations at the end of the program, it was concluded that they gained a better understanding of social enterprise after participating in this community service activity.